Effect of University Social Capital on Working Students' Dropout Intentions: Insights from Estonia - Mohammad Abu Sayed Toyon (MDPI AG, 2024)
This study investigates the role of social capital within the university context in retaining working students. It specifically examines the effects of university social capital factors-such as teacher-student relationships, peer networks, and support services-on the dropout intentions of working students, emphasizing the mediating role of employability trust. Using a sample of 1902 working students from the Eurostudent VII survey, this study employed factor analysis techniques and structural equation modeling to derive its findings. The results indicated that university social capital significantly reduces dropout intentions among working students. Strong teacher-student relationships, satisfaction with support services, robust peer networks, and high employability trust positively influence this social capital. There is a statistically significant negative association between teacher-student relationships, peer networks, employability trust, and dropout intentions. Furthermore, the findings reveal that without enhancing students' employability trust, the effectiveness of support services might be limited. These findings not only contribute to the discourse on student retention and the development of university social capital but also provide practical insights for higher education strategies aimed at supporting working students.